Evidence of high-efficiency cross fertilization in Eimeria acervulina revealed using two lines of transgenic parasites. Issue 2 (February 2023) - Liu, Jie; Shi, Fangyun; Zhang, Yuanyuan; Tang, Xinming; Wang, Chaoyue; Gao, Yang; Suo, Jingxia; Yu, Ying; Chen, Linlin; Zhang, Ning; Sun, Pei; Liu, Xianyong; et al.
Graphical abstract: Highlights: We generated two transgenic Eimeria acervulina lines expressing constitutive and sex-specific fluorescent markers. A genetic cross with a higher infective dose at an equal oocyst ratio could increase the cross-fertilization rate. Similar numbers of functional gametocytes from parents could increase the cross-fertilization rate. Abstract: Eimeria species are apicomplexan parasites with a direct life cycle consisting of a replicative phase involving multiple rounds of asexual replication in the intestine or other organs including kidneys, liver, and gallbladder, depending on the species, followed by a sexual phase or gamogony involving the development and fertilization of gametes, an essential process for Eimeria transmission. Recent advances in the genetic manipulation of these parasites made it possible to conduct genetic crosses combined with genomic approaches to elucidate the genetic determinants of Eimeria development, virulence, drug resistance, and immune evasion. Here, we employed genetic techniques to generate two transgenic Eimeria acervulina lines, EaGAM56 and EaHAP2, each expressing two unique fluorescent proteins, with one controlled by a constitutive promotor for cross-efficiency analysis and the other by a male or female gametocyte stage-specific promoter to observe sexual development. The expression of fluorescent proteins in the transgenic lines was analyzed in different developmental stages of the E. acervulina life cycle by immunoblotting and by examination of frozen sections using fluorescence microscopy. The effect of infective doses on cross-fertilization was further investigated by conducting several genetic crosses between the two transgenic lines at different doses and ratios. Two transgenic lines expressing constitutive and gametocyte-specific fluorescence proteins were generated and characterized. These transgenic parasites display synchronous development in chickens, comparable with that of the wild type. Genetic crosses between the two transgenic parasites showed that a high rate of oocysts co-expressing the two reporters could be achieved following inoculation with high doses of infective oocysts. We further showed that the proportion of co-transfected oocysts can be modulated by altering the ratio of the transgenic parental lines. Higher infective doses and similar numbers of functional gametocytes from the parents increase the rate of cross-fertilization. Our data highlight the usefulness of genetic manipulation and fluorescently-labeled transgenic gametocytes as tools to study Eimeria development and to elucidate the factors that modulate sexual development. This work sets the stage for the implementation of novel approaches to investigate other aspects of Eimeria pathogenesis, virulence, and drug susceptibility and resistance.